A synchrotron radiation study of high-lying excited states of matrix-isolated atomic magnesium - Kerins, Paul; Healy, Brendan; McCaffrey, John G. (Физика низких температур, 2000)
Previous steady-state and time-resolved luminescence spectroscopy of 3p ¹P₁ atomic magnesium, isolated in thin film samples of the solid rare gases, has been extended to include the higher energy 4p ¹P₁ excitation. Well resolved site splittings have been recorded in Mg/Ar samples for excitation to the 4p ¹P₁ level. A small red shift in the absorption energy to the 4p ¹P₁ level for Mg/Ar contrasts with a small blue shift on absorption to the 3p ¹P1 level. Direct emission from the 4p ¹P1 level is not observed in any of the rare gas matrices, instead intense emission from the low energy 3p ¹P1 level is. Measurements of the emission decay curves in Mg/Ar have revealed slow rates in the steps feeding the 3p ¹P₁ level following 4p ¹P₁ excitation. The reason for the differential shifting of the 4 p ¹P₁ and 3p ¹P₁ levels as well as the lack of direct 4p ¹P₁ emission is thought to be related to the strong binding interaction between Mg in the 4p ¹P₁ state and the rare gases.